(untitled) (TAJ: Journal of Teachers Association, 2018)
Aim: To assess effectiveness of Hayman suture to control postpartum haemorrhage due to placenta praevia during caesarean section Methods: It is a cross sectional observational study performed in Rajshahi Medical College Hospital, tertiary level hospital, from January 2016 to December 2016. It included 32 patients with PPH following placenta praevia during elective& emergency caesarean section (C/S). All 32 patients underwent horizontal compression suture (bilateral anteroposterior compression) of lower uterine segment. Vicryl 0 tapercut needle was used. All patients were followed postpartum for evaluation of uterine cavity and menstrual cycles. Results Hayman suture was applied in 32 cases. In 27 cases Hayman suture was the only intervention. Hayman with uterine artery ligation required in 2 cases. In 1 patient along with Hayman B-lynch compression suture was given and 2 patients required total hysterectomy. Conclusion: The quick and simple Hayman technique seems to be effective, safe, lifesaving method in stopping hemorrhage due to placenta praevia. TAJ 2017; 30(1): 66-69